'The Gallaunts of Fawey': a case study of Fowey during the Hundred Years' War, c.1337–1399. Issue 248 (28th March 2017) - Drake, S. J.
Abstract: This article explores the influence of the Hundred Years' War on Fowey between c .1337 and 1399. In so doing, it employs naval pay rolls to study the contribution the town made to royal fleets and considers the mechanisms which the Crown employed to defend the port from enemy raids. It also examines the degree to which the war was extended though the agency of 'pirates'. The article argues that the conflict had an all‐pervasive effect upon Fowey, but that the costs incurred by the port and its people as a result of this were by no means crippling.